2019
DOI: 10.4103/ams.ams_3_19
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of spirulina along with different physiotherapeutic modalities in the management of oral submucous fibrosis

Abstract: Context: Oral submucous fibrosis (OSMF) is an insidious, chronic, disabling disease that mainly affects the oral mucosa. Spirulina is a freshwater microalga which is considered as superfood by the WHO. Due to its antioxidant, anti-inflammatory, and immunomodulating properties, spirulina has shown promising results in the management of OSMF. A wide range of treatment modalities have been tried ranging from medical, physical, or surgical interventions, but combinations of these have shown better res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Spirulina strongly induces antioxidant enzyme activity, helps to prevent lipid peroxidation and DNA damage, and scavenges free radicals this antioxidant activity makes it a potential treatment for different diseases as chronic obstructive pulmonary disease, muscle damage, and cardiovascular diseases among others 45 . Different studies included in this review demonstrate that spirulina together with mouth exercises improves significantly all the parameters analyzed in this review 22 and it has even been shown, as mentioned above, that spirulina alone shows better results in mouth opening than aloe vera 30 . Although less common, this compound has also been shown to be effective in other oral pathologies such as oral lichen planus and periodontitis 46,47 …”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Spirulina strongly induces antioxidant enzyme activity, helps to prevent lipid peroxidation and DNA damage, and scavenges free radicals this antioxidant activity makes it a potential treatment for different diseases as chronic obstructive pulmonary disease, muscle damage, and cardiovascular diseases among others 45 . Different studies included in this review demonstrate that spirulina together with mouth exercises improves significantly all the parameters analyzed in this review 22 and it has even been shown, as mentioned above, that spirulina alone shows better results in mouth opening than aloe vera 30 . Although less common, this compound has also been shown to be effective in other oral pathologies such as oral lichen planus and periodontitis 46,47 …”
Section: Discussionmentioning
confidence: 80%
“…A total of 97 articles were obtained from the initial search process: All the studies measured the progression of the OSMF in terms of mouth opening, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] 17 articles reported on burning sensation, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] 16 articles discussed tongue protrusion [15][16][17][18]21,26,28,31,33 and 8 articles examined cheek flexibility. 16,18,[21][22]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spirulina in combination with isometric exercises/threaded tapered screw/mouth stretching device [35] antioxidant, anti-inflammatory and immuno-modulation 3 months BID Oral…”
Section: Sl No Drugsmentioning
confidence: 99%